Viralitas Atlet sebagai Strategi Komunikasi Pemasaran dalam Penerimaan Mahasiswa Baru Universitas Dian Nuswantoro - Shalma Nursyahidha; Lintang Ratri Rahmiaji (Dinasti Research, 2026)
The phenomenon of competition between universities has encouraged various institutions to implement creative and easily disseminated digital marketing approaches on social media. This study aims to analyze how viral strategies are designed, implemented, and interpreted in student admissions promotional activities. The research employed a qualitative approach with an interpretive paradigm and a case study method. Data were obtained through in-depth interviews, observations, and documentation of the Admissions and Promotions Bureau, Public Relations and Protocol Bureau, Student Affairs Bureau, and digital campaign materials at Dian Nuswantoro University. Data analysis was conducted through data reduction, categorization, and interpretation to understand the virality strategies employed. The results of the study show that the use of athlete figures as a representation of campus identity, combined with visual narratives,storytelling, and distribution of social media content can build traction, increase audience engagement, and expand promotional reach. Virality stems not only from creative content but also from the message's relevance to the target audience.platformsocial media and publicity momentum. This strategy strengthens the institution's image and supports the effectiveness of marketing communications in the new student admissions process.